4,6-Diazido-N-(2,4,6-trinitrophenyl)-1,3,5-triazin-2-amine (TNADAzT) and Its Silver Salt - Synthesis and Characterization - Musil, Tomáš; Matyáš, Robert; Zeman, Svatopluk; Růžička, Aleš; Lyčka, Antonín; Majzlík, Jiří; Vala, Roman; Knotek, Petr (Institut Przemyslu Organicznego, 2017)
4,6-Diazido-N-(2,4,6-trinitrophenyl)-1,3,5-triazin-2-amine (TNADAzT) and its silver salt (AgTNADAzT) were prepared and characterized. Elemental analysis, FTIR, NMR, DSC, AAS and X-ray diffraction were used for analytical characterization. The sensitivities of TNADAzT and AgTNADAzT were determined and compared with common explosives and MTX-1. The crystal density of TNADAzT is 1.794 g.cm(-3) and its heat of formation 899 kJ.mol(-1). The sensitivity of TNADAzT to impact and friction slightly exceeds PETN; the sensitivity to electrostatic discharge is lower than RDX. The sensitivity of AgTNADAzT is on the level of a primary explosives (between mercury fulminate and PETN). The initiation efficiency of AgTNADAzT is higher than 200 mg (acceptor PETN compressed by 64-70 MPa) and therefore excludes it from practical use as a primary explosive in detonators.
4,6-Diazido-N-(2,4,6-trinitrophenyl)-1,3,5-triazin-2-amin (TNADAzT) a jeho stříbrná sůl - syntéza a charakterizace
Keywords: azido derivative of triazine; silver salt; sensitivity; MTX-1; X-ray; azido deriváty triazinu; stříbrná sůl; citlivost; MTX-1; roentgenografie